2013
DOI: 10.1174/113564013806631255
|View full text |Cite
|
Sign up to set email alerts
|

El desarrollo de neoformaciones a través del juego y del cuento en niños preescolares

Abstract: El presente trabajo tiene por objetivo establecer los efectos de un método educativo alternativo para niños preescolares, basado en las premisas teóricas de la psicología histórico-cultural. El programa incluyó actividades de juego temático de roles introducido por etapas y lectura y análisis de cuentos. Para la organización del juego se tomaron aspectos específicos de la propuesta de Elkonin (1980) y para el análisis de cuentos se consideró la propuesta de Tsvetkova (1999). Los niños del grupo experimental y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
0
4
0
3
Order By: Relevance
“…The findings of this research concur with the perspective of other authors, confirming that social role play must be developed with the participation of adults, who guide the children in the actions to perform it (Talizina, 2009;González et al, 2011;Ruíz and Abad, 2011). It is also confirmed that the role play promotes the development of mental and social skills in preschool age, since children not only acquire appropriate information, but will also be able to reflect, re-create, develop new ideas, and create mental images and concepts, regulating their own emotions efficiently (Elkonin, 1980;García et al, 2013;González et al, 2014), facilitating the separation of thought from actions and objects (Bodrova and Leong, 2008).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The findings of this research concur with the perspective of other authors, confirming that social role play must be developed with the participation of adults, who guide the children in the actions to perform it (Talizina, 2009;González et al, 2011;Ruíz and Abad, 2011). It is also confirmed that the role play promotes the development of mental and social skills in preschool age, since children not only acquire appropriate information, but will also be able to reflect, re-create, develop new ideas, and create mental images and concepts, regulating their own emotions efficiently (Elkonin, 1980;García et al, 2013;González et al, 2014), facilitating the separation of thought from actions and objects (Bodrova and Leong, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…First, the adult regulates it with her/his language, then the child controls himself with his external language and finally controls himself with his internal language (Luria, 1984 ; González et al, 2011 ; Rabello, 2014 ). This control is present during play in its organization, execution, and verification (García et al, 2013 ). This leads to the minor developing reflexive thinking, which manifests itself when the child manages to transform his own verbal expression and actions (González et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…O papel do adulto é destacado por Leontiev (1987) como essencial no desenvolvimento da hierarquia de motivos e da atividade voluntária, neoformação advinda da atividade-guia pré-escolar destacada por autores como García et al (2013). Segundo Talizina (2009), quando a criança realiza uma atividade lúdica reduzida afeta o desenvolvimento desse processo.…”
Section: As Contribuições Da Psicologia Histórico--cultural Para O Pr...unclassified
“…Por ello es por lo que entre rito y juego hay una veta de homología. Tal como se ha señalado en la literatura de la psicología del desarrollo (Chamorro, 2010;García, 2009), cuando los niños juegan roles, que deberán jugar como adultos (Bateson, 1972;Callois, 1958). La liturgia tendría así elementos de una experiencia lúdica de adultos.…”
Section: Liturgia Como Juegounclassified